2016
DOI: 10.14218/jcth.2016.00004
|View full text |Cite
|
Sign up to set email alerts
|

The Evolving Nature of Hepatic Abscess: A Review

Abstract: Hepatic abscess (HA) remains a serious and often difficult to diagnose problem. HAs can be divided into three main categories based on the underlying conditions: infectious, malignant, and iatrogenic. Infectious abscesses include those secondary to direct extension from local infection, systemic bacteremia, and intra-abdominal infections that seed the portal system. However, over the years, the etiologies and risks factors for HA have continued to evolve. Prompt recognition is important for instituting effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 55 publications
4
59
1
2
Order By: Relevance
“…With regard to epidemiologic characteristics, our findings in elderly patients were also consistent with the literature, with a predominance of women in the older group and men in the younger group [8, 21, 22]. This may be due to the different life expectancies between sexes as well as the greater prevalence of chronic liver disease among younger patients in our study.…”
Section: Discussionsupporting
confidence: 91%
“…With regard to epidemiologic characteristics, our findings in elderly patients were also consistent with the literature, with a predominance of women in the older group and men in the younger group [8, 21, 22]. This may be due to the different life expectancies between sexes as well as the greater prevalence of chronic liver disease among younger patients in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Pyogenic liver abscesses are usually classified by presumed route of hepatic invasion: (1) biliary tree, (2) portal vein, (3) hepatic artery, and (4) direct extension from contiguous focus of infection ( Fig. 1 ) [ 8 ]. The most common etiologies are unknown cryptogenic (primary) origin and infection by biliary route [ 9 10 ].…”
Section: Route Of Hepatic Invasionmentioning
confidence: 99%
“…It was reported that liver biopsy could be considered to obtain liver tissue sample for bacterial culturing, however, it is not easy to perform in children owing to its invasiveness. Some rare diagnostic methods include: bile culture is invasive, and liver puncture is not guaranteed to take bile unless there is a definite bile lake (15).…”
Section: Discussionmentioning
confidence: 99%